PENINGKATAN PEMBELAJARAN MENULIS TEKS LAPORAN HASIL OBSERVASI MELALUI NEIGHBORHOOD WALK STRATEGY SISWA KELAS X-1 SMA NEGERI 1 SOPPENG RIAJA KABUPATEN BARRU - Lilis Suryani (STKIP Paris Barantai, 2016)
The study is a clasroom action research which aims at describing the improfmen of learning activiyy of report writing based on observation reselt and the improfment of learning result of report writing based on observation result of class x-1 student at SMAN 1 Soppeng Riaja by implementing Neighborhood walk strategy model. The samples were 36 students of class X-1 AT sman 1 Soppeng Riaja of academic year 2014-2015. The study was conducted in two cycles, namely cycle l and cycle ll. Eachcycle consisted of two meeatings. At the implementation phased in cycle I and cycle ll, observation shet and test of report writing based on observation result were used to collect the data needed and as the benchmark of students’ality in writing report based on observation result based on the minimal completensess criteria of 75. The results of the study reveal that neighborhood walk strategy can improve report writing ability based on observation result of class X-1 student at SMAN 1 Soppeng Riaja at the stages of planning, action,observation, and evaluation. The subject teacher is confirmed as successful to improve and conduct the planning which gives better value. At the action stage, the student expecienced atitude changes to better ones. At the evaluation stage, the result of report writing based on observation result test by considering content, text structure, vocabulary,sentence, and mechanics aspectsindicated that at cycle I students have achieved the competeness levelin report writing based on observation result learning. The conclusion based on the result is the Neighborhood Walk Strategy model can improve report writing based on observation result of class X-1 students at SMAN 1 Soppeng Riaja after conducting the cycless twice. Keywords: Write Text Report And Observations